Extreme values analysis for Asean stock exchanges - Chaiboonsri C. (2017)
© Chukiat Chaiboonsri, Prasert Chaitip, 2016. This paper aims to provide a precise estimation for prediction the extreme value of set index points of the ASEAN stock markets. The time series data of set index point from 3 markets in ASEAN Exchange such as the Stock Exchange of Thailand, Kuala Lumpur Stock Exchange (KLSE) and Exchange LTD in Singapore were used. Time series data was used to predict the extreme value of set index points for 1987-2014 (annual data). The precise estimation approach was used applying the Bayesian inference approach. The research result confirmed that the prediction value of each stock exchange is reasonable to prevent the financial crisis after 2015.